Drivers of Sustainable Rural Growth and Poverty Reduction in Central America : Guatemala Case Study, Volume 1. Executive Summary and Main Text - World Bank (Washington, DC, 2013)
This regional study encompasses three Central American countries: Nicaragua, Guatemala and Honduras. The focus of this report is Guatemala. The study is motivated by several factors: First is the recognition that sub-national regions are becoming increasingly heterogeneous, and economically differentiated as part of ongoing processes of development and diversification, with some areas advancing, and others being left behind. Second is the acceptance that one rural strategy does not fit all; design of an appropriately tailored rural strategy requires understanding the assets, markets, and institutions that frame household opportunities and livelihood strategies. Third, rural heterogeneity requires identification of sufficiently homogeneous areas and household types to facilitate policy formulation, investment strategies, and project design. Fourth, there is a need to bridge the gap between conceptual strategies, and their timely implementation in order to obtain tangible and sustainable results. To this end, it is necessary to identify the appropriate sequencing, and complementary of investments in assets needed to drive growth and reduce poverty. The study's focus on assets is appropriate given historically stark inequalities in the distribution of productive assets among households in the region. Such inequalities are likely to constrain how the poor share in the benefits of growth, even under appropriate policy regimes. Rural poverty in Guatemala is characterized by three important features. First, geographic isolation, caused by varied topography, and inadequate transport networks, is an important correlate of poverty. The second dominant feature of rural poverty is ethnic exclusion. Poverty rates are far higher among indigenous groups and groups whose primary language is not Spanish. Third, rural poverty is concentrated in particular areas: that is, it has a particularly strong spatial dimension in Guatemala. Findings indicate that the high degree of overlap between high poverty rates, and high poverty densities in areas such as the Western Altiplano, means that investments there should reach significant proportions of the country's rural poor. Thus, to generate substantial gains in poverty reduction and broad-based growth, complementarities between productive, social, and location-specific assets must be addressed. Specifically, the report focuses on access to land, and strong local level institutions, and social capital, to compensate for lack of physical assets. This also requires a move from geographically untargeted investments in single assets, to a more integrated and geographically based approach of asset enhancement, with proper complementarities.